Anatomical variations of the ischitic nerve associated with the piriform muscle in fetus and childrens until 1 year of post-natal life: DOI: 10.15343/0104-7809.20174104581587 - Palmas Fernandes Greco, Fernanda (2017)
The sciatic nerve and the piriformis muscle are closely related structures due to their anatomy, in which the nerve passes below the muscle in its normal path. For this reason, any anatomical changes can cause sciatic pain. Considering the importance of knowing the variations of these two structures, we aim to evaluate and describe the relationship of the sciatic nerve with the piriformis muscle in cadavers of human fetuses and of children up to one year of postnatal life. Eighty-seven individuals preserved by the Giacomini method, all belonging to the didactic collection of the Department of Anatomy of the Institute of Biomedical Sciences of the University of São Paulo (DA / ICB-USP), were dissected. Of the individuals studied, 70 had fetal ages ranging from 18 to 28 weeks of intrauterine life (IU) and 17 individuals from stillbirth to one year of postnatal life. Of the total, 40 were male and 47 female. 19 individuals presented variations: 14 with the sciatic nerve dividing before their arrival in the region of the piriformis muscle and 5 with a variation in the path of the sciatic nerve. No statistical correlations were found for the incidence of anatomical variations of the sciatic nerve with age, gender or antimere.